Las vestales, los "sacra", los "doliola" y el "sascellum" en la toma de Roma por los galos el 390 a C (Estudios Humanísticos. Filología, 1990)
Las vestales, los "sacra", los "doliola" y el "sascellum" en la toma de Roma por los galos el 390 a C